Recovery of function following hip resurfacing arthroplasty: a randomized controlled trial comparing an accelerated versus standard physiotherapy rehabilitation programme. (September 2013) - Barker, Karen L; Newman, Meredith A; Hughes, Tamsin; Sackley, Cath; Pandit, Hemant; Kiran, Amit; Murray, David W
Objective: To identify if a tailored rehabilitation programme is more effective than standard practice at improving function in patients undergoing metal-on-metal hip resurfacing arthroplasty. Design: Randomized controlled trial. Setting: Specialist orthopaedic hospital. Subjects: 80 men with a median age of 56 years. Interventions: Tailored post-operative physiotherapy programme compared with standard physiotherapy. Main Outcomes: Primary outcome – Oxford Hip Score (OHS), Secondary outcomes: Hip disability and Osteoarthritis Outcome Score (HOOS), EuroQol (EQ-5D-3L) and UCLA activity score. Hip range of motion, hip muscle strength and patient selected goals were also assessed. Results: At one year the mean (SD) Oxford Hip Score of the intervention group was higher, 45.1 (5.3), than the control group, 39.6 (8.8). This was supported by a linear regression model, which detected a 5.8 unit change in Oxford Hip Score ( p < 0.001), effect size 0.76. There was a statistically significant increase in Hip disability and Osteoarthritis Outcome Score of 12.4% ( p < 0.0005), effect size 0.76; UCLA activity score differed by 0.66 points ( p < 0.019), effect size 0.43; EQ 5D showed an improvement of 0.85 ( p < 0.0005), effect size 0.76. A total of 80% (32 of 40) of the intervention group fully met their self-selected goal compared with 55% (22 of 40) of the control group. Hip range of motion increased significantly; hip flexion by a mean difference 17.9 degrees ( p < 0.0005), hip extension by 5.7 degrees ( p < 0.004) and abduction by 4 degrees ( p < 0.05). Muscle strength improved more in the intervention group but was not statistically significant. Conclusions: A tailored physiotherapy programme improved self-reported functional outcomes and hip range of motion in patients undergoing hip resurfacing.